2009
DOI: 10.1056/nejmoa0902413
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Continuous Renal-Replacement Therapy in Critically Ill Patients

Abstract: In critically ill patients with acute kidney injury, treatment with higher-intensity continuous renal-replacement therapy did not reduce mortality at 90 days. (ClinicalTrials.gov number, NCT00221013.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
403
3
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,250 publications
(426 citation statements)
references
References 17 publications
17
403
3
3
Order By: Relevance
“…Some reasons for this difference might be the result of previous studies that focused on identifying the indications and timing of renal replacement therapy [11,12], CRRT modalities in critically ill patients [2,13], CRRT dose [14,15,16] and the impact of anticoagulation on filter life during CRRT [17,18]. Therefore, any reporting of haemodynamic changes at the time of initiation of CRRT may only be an incidental finding.…”
Section: Discussionmentioning
confidence: 99%
“…Some reasons for this difference might be the result of previous studies that focused on identifying the indications and timing of renal replacement therapy [11,12], CRRT modalities in critically ill patients [2,13], CRRT dose [14,15,16] and the impact of anticoagulation on filter life during CRRT [17,18]. Therefore, any reporting of haemodynamic changes at the time of initiation of CRRT may only be an incidental finding.…”
Section: Discussionmentioning
confidence: 99%
“…The Acute Renal Failure Trial Network (ARFTN) study demonstrated that there is no benefit of intermittent haemodialysis six times a week vs three times a week or CVVHDF at a dose of 35 ml/kg/h vs 20 ml/kg/h [26]. Similarly The Randomized Evaluation of Normal versus Augmented Level (RENAL) replacement therapy study failed to show any advantage of 40 ml/kg/h CVVHDF vs 20 ml/kg/h [27].…”
Section: Dose Of Rrtmentioning
confidence: 99%
“…Whether the same applies for a dose of 35 ml/kg/h remains to be answered. In the recent Randomized Evaluation of Normal versus Augmented Level (RENAL) study [10], 1,508 critically ill patients with AKI were randomized to receive a CVVHDF dose of either 25 or 40 ml/kg/h. No difference in 90-day mortality, the primary endpoint of the study, was observed between the two groups.…”
Section: Update On Recent Negative Trials In Aki In Critically Ill Pamentioning
confidence: 99%
“…Moreover, mortality in sepsis-induced AKI is significantly higher than in non-septic AKI [4,5,6]. While several milestone studies in the last decade [7,8] have shown that the dose of therapy was of paramount importance regarding mortality, more recent trials have challenged this concept [9,10]. It stands to reason that a critical minimum dose is still desirable and that below this defined dose, mortality will be affected [11,12].…”
Section: Introductionmentioning
confidence: 99%